The Presumption of Innocentness in the Perspective of Human Rights (Case Study of Persecution of Tempo Journalist Nurhadi) - Aulia Wisi Putri Utami (Faculty of Law Universitas Muhammadiyah Purwokerto, 2022)
AbstractThe press is all mass communication media that transmit thoughts in written and spoken words made by journalists/journalists. Article 8 of Law no. 40 of 1999 concerning the Press and the Journalistic Code of Ethics for Indonesian journalists states that press freedom is guaranteed as a human right of citizens. Journalists in carrying out their profession are recorded in the law. That in carrying out their profession, journalists get legal protection. However, in reality, violence by investigators against journalists still occurred in May 2021, when journalists were interrogated with physical violence by investigators.In contrast, positive Indonesian law states that the presumption of innocence has been formulated in several other laws and regulations. This principle can serve as a guide for carrying out investigations by reasonable procedures. This issue is about the principle of presumption of innocence in Indonesia and how the presumption of innocence from a human rights perspective is in the case of persecution of journalist Nurhadi by the Police. The research method used is a normative juridical research method to obtain results regarding the Regulation of the presumption of innocence in detail in Indonesia and an understanding of the principle of the presumption of innocence as an embodiment of human rights that protect the overall dignity and worth that must uphold.Keywords: Principles of Presumption of Guilt, Human Rights, Law AbstrakPers adalah semua media mass communi cations yang memancarkan fikiran baik dengan kata-kata tertulis maupun dengan kata-kata lisan yang dibuat oleh wartawan/jurnalistik. Pasal 8 Undang-Undang No. 40 Tahun 1999 tentang Pers dan Kode Etik Jurnalistik wartawan Indonesia, mengatakan bahwa kemerdekaan pers dijamin sebagai hak asasi warga negara. Wartawan dalam menjalankan profesi yaitu tercatat di undang-undang bahwa dalam melaksanakan profesinya wartawan mendapatkan perlindungan hukum. Namun kenyataannya kekerasaan oleh penyidik kepada wartawan masih terjadi pada Mei 2021 saat wartawan di introgasi dengan kekerasan fisik oleh penyidik. Padahal hukum positif Indonesia menyatakan bahwa asas praduga tidak bersalah (presumption of innocence) telah dirumuskan dalam beberapa undang-undang dan peraturan lainnya, dimana asas tersebut dapat menjadi tuntunan untuk menjalankan penyidikan sesuai dengan prosedur yang baik. Sesuai dengan hal tersebut, maka timbulah sebuah masalah mengenai bagaimana pengaturan asas praduga tidak bersalah di Indonesia, dan bagaimana asas praduga tidak bersalah dalam perspektif hak asasi manusia pada kasus penganiayaan wartawan Nurhadi oleh oknum kepolisian. Metode penelitian yang digunakan adalah metode penelitian yuridis normatif untuk memperoleh hasil mengenai pengaturan asas praduga tidak bersalah secara rinci di Indonesia dan pemahaman asas praduga tak bersalah merupakan perwujudan hak asasi manusia yang memberikan perlindungan terhadap keseluruhan harkat dan martabat yang wajib dijunjung tinggi.Kata Kunci : Asas Praduga Tidak Bersalah, Hak Asasi Manusia, Undang-Undang